The role of IL-1 inhibition in systemic juvenile idiopathic arthritis: current status and future perspectives - Toplak N; Blazina Š; Avčin T (Dove Medical Press, 2018)
Nataša Toplak,1,2 Štefan Blazina,1 Tadej Avčin1,2 1Department of Allergology, Rheumatology and Clinical Immunology, University Children’s Hospital, University Medical Centre Ljubljana, Ljubljana, Slovenia; 2Faculty of Medicine, University of Ljubljana, Ljubljana, Slovenia Abstract: The pathogenesis, clinical course, and response to treatment in systemic juvenile idiopathic arthritis (SJIA) differ from other types of juvenile idiopathic arthritis and are similar to other interleukin-1 (IL-1)-mediated diseases. The main cytokine involved in the pathogenesis of SJIA is IL-1β, which can be neutralized by targeted anti-IL-1 therapy. In SJIA, no antibodies have been found and there is growing evidence that it is mainly an autoinflammatory and not an autoimmune disease. Before the era of biologic therapy, treatment of SJIA was primarily based on long-term treatment with high doses of glucocorticosteroids (GCS). The side effects of GCS could have a significant impact on the outcome of the disease and could cause long-term damage. Treatment with anti-IL-1 agents early in the disease course has revolutionized the management principles of SJIA. However, not all SJIA patients respond equally well to anti-IL-1 therapy, and it has been shown that age at the onset of disease, duration of the disease, number of affected joints, neutrophil count, and ferritin level can predict the response to anti-IL-1 therapy. In particular, an elevated ferritin level should prompt testing for macrophage activation syndrome (MAS), the most severe complication of SJIA. Anti-IL-1 therapy has been shown to be effective also in patients with MAS. Although anti-IL-1 agents are currently not recommended as first-line treatment, there is growing evidence that anti-IL-1 agents introduced at the beginning of SJIA could enable lower doses and a shorter duration of GCS therapy, change the long-term disease outcome, and even influence molecular disease patterns. There are currently three anti-IL-1 agents available: anakinra, canakinumab, and rilonacept. In this review, we present the current knowledge on the pathogenesis of SJIA, the rational for anti-IL-1 treatment, and future perspectives on the treatment of SJIA. Keywords: anti-IL-1 therapy, anakinra, canakinumab, rilonacept, systemic juvenile idiopathic arthritis